2010
DOI: 10.1007/s10562-010-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized 1,1,3,3-Tetramethylguanidine Ionic Liquids as the Catalyst for Synthesizing Propylene Glycol Methyl Ether

Abstract: In this work, we immobilized ionic liquid 1,1,3,3-tetramethylguanidium lactate on two solid supports, bentonite and SBA-15, by different methods. The prepared materials were used to catalyze the reaction of propylene oxide and methanol to produce propylene glycol methyl ether. 1-Methoxy-2-propanol was the predominant product. The influence of the amount of the catalyst, molar ratio of the reactants, reaction temperature and time on the yield and selectivity was studied. The two catalysts were proved to be effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Different catalytic systems relevant to this process are reported in the literature. These systems include alkaline catalysts (hydroxides of alkali and alkaline‐earth metals),, amino‐functionalized SiO 2 , immobilized ionic liquid 1,1,3,3‐tetramethylguanidinium lactate on bentonite and SBA‐15 (IL/Support),, M x O y (M – Cu, Fe, Zn, Sn, and Ni), MgO,, metal phosphate molecular sieves, Al‐, Ga‐, Zr‐, and Zr, Al‐pillared clays (PILCs), natural and synthetic layered double hydroxides (LDHs) …”
Section: Introductionmentioning
confidence: 99%
“…Different catalytic systems relevant to this process are reported in the literature. These systems include alkaline catalysts (hydroxides of alkali and alkaline‐earth metals),, amino‐functionalized SiO 2 , immobilized ionic liquid 1,1,3,3‐tetramethylguanidinium lactate on bentonite and SBA‐15 (IL/Support),, M x O y (M – Cu, Fe, Zn, Sn, and Ni), MgO,, metal phosphate molecular sieves, Al‐, Ga‐, Zr‐, and Zr, Al‐pillared clays (PILCs), natural and synthetic layered double hydroxides (LDHs) …”
Section: Introductionmentioning
confidence: 99%
“…The yields of 1-MP were 95−96% and 96−97% in the presence of IL/bentonite and IL/SBA-5, respectively. 13 The use of mesoporous silica MCM-41 as a support for ILs was proposed. 14 Thus, application of cetyltrimethylammonium hydroxide ([CTA]OH) encapsulated in MCM-41 has led to a yield of 92% with 92−93.5% selectivity toward 1-MP at 110 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several recent studies have shown that the reaction temperature could be reduced by the application of nitrogen containing compounds. Liang et al showed that the reaction temperature can be decreased to 110–120 °C in the presence of the immobilized ionic liquid (IL) 1,1,3,3-tetramethylguanidium lactate on bentonite and SBA-15 (IL/support). The yields of 1-MP were 95–96% and 96–97% in the presence of IL/bentonite and IL/SBA-5, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group reported that the IL 1,1,3,3‐tetramethylguanidium lactate ([TMG][Lac]) could be immobilized on bentonite and SBA‐15 as solid catalyst. It is found that the obtained materials were excellent heterogeneous catalysts for the reaction of methanol with propylene oxide to produce propylene glycol methyl ether …”
Section: Preparation Of Supported Catalysts With Ilsmentioning
confidence: 99%